(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
Comparison of perceptions according to the definitions of the notion "tourism destination" is carried out in this article. The tourism destination is presented as a key component of tourism development, as a spatial system that summarizes, coordinates, carries and expresses this development. A tourism destination is viewed as a spatial basis that is itself considered a tourist resource and contains tourist resources in itself. In this context, the article theorizes the geographical basis of a tourism destination and substantiates the components of its practical manifestation/significance. The article provides answers to the following questions: is a tourism destination a kind of geographical space and what kind of variety is it?